2019
DOI: 10.1002/acr.23829
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Foot Pain Across an International Consortium of Population‐Based Cohorts

Abstract: Objective Despite the potential burden of foot pain, some of the most fundamental epidemiologic questions surrounding the foot remain poorly explored. The prevalence of foot pain has proven to be difficult to compare across existing studies due to variations in case definitions. The objective of this study was to investigate the prevalence of foot pain in several international population‐based cohorts using original data and to explore differences in the case definitions used. Methods Foot pain variables were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
1
25
1
5
Order By: Relevance
“…Our study shows that patients with RA are more likely to present structural alterations in the foot and hence to experience physical and/or psychosocial deterioration than when this condition is absent. 34 Furthermore, the long-term evolution of the disease may be directly related to psychosocial and emotional perceptions. It should also be taken into account that in our study groups most of the patients were female, although this reflects their prevalence among the general population affected by RA and foot pain.…”
Section: Open Accessmentioning
confidence: 99%
“…Our study shows that patients with RA are more likely to present structural alterations in the foot and hence to experience physical and/or psychosocial deterioration than when this condition is absent. 34 Furthermore, the long-term evolution of the disease may be directly related to psychosocial and emotional perceptions. It should also be taken into account that in our study groups most of the patients were female, although this reflects their prevalence among the general population affected by RA and foot pain.…”
Section: Open Accessmentioning
confidence: 99%
“…Our study has added to the knowledge of not only examining prevalence, but also pain perception and daily experiences of chronic foot pain in both men and women in various occupations. These differences have been widely reported in previous studies 14,22,23,31 , and have been attributed to other factors such as foot wearing habits, especially in women and prolonged standing and pain perception 12,31 . Women are more likely to report musculoskeletal pain in general 31 , and pain perception 31 .…”
Section: Discussionmentioning
confidence: 73%
“…These differences have been widely reported in previous studies 14,22,23,31 , and have been attributed to other factors such as foot wearing habits, especially in women and prolonged standing and pain perception 12,31 . Women are more likely to report musculoskeletal pain in general 31 , and pain perception 31 . In addition to the women reporting more foot pain, other studies have shown that moderate-tosevere foot pain is highly prevalent in a university-educated population and is independently associated with women 7 .…”
Section: Discussionmentioning
confidence: 73%
“…Both progression (defined as a score of 2 at year 6 and 3 at year 23) and worsening (defined as a score of 0, 1, or 2 at year 6, increasing to higher score of 1, 2, or 3 at year 23) of OA were more evident in the right first MTP joints. Very few studies have reported on the epidemiology of foot OA, which makes comparison of the cohort data that does exist in this field challenging (30). Figures for radiographic foot OA prevalence estimates vary considerably depending on the population, the radiographic views taken, which foot joints are examined, the grading systems applied, and whether symptomatic or asymptomatic foot OA is studied (9,26).…”
Section: Discussionmentioning
confidence: 99%